Unraveling the gut microbiota's role in salt-sensitive hypertension: current evidences and future directions - Wang, Li; Hu, Jihong (Frontiers in Cardiovascular Medicine, 2024)
The gut microbiota plays a pivotal role in both maintaining human health and in the pathogenesis of diseases. Recent studies have brought to light the significant correlation between gut microbiota and hypertension, particularly focusing on its role in the development and advancement of SSH, a subtype characterized by elevated blood pressure in response to high salt consumption. The complexity of SSH's etiology is notable, with dysbiosis of the gut microbiome identified as a crucial contributing factor. The gut microbiota participates in the occurrence and development of SSH by affecting the host's immune system, metabolic function, and neuromodulation. Investigations have demonstrated that the gut microbes regulate the development of SSH by regulating the TH17 axis and the activity of immune cells. Moreover, microbial metabolites, such as short-chain fatty acids, are implicated in blood pressure regulation and affect the development of SSH. There is evidence to show that the composition of the gut microbiome can be altered through prebiotic interventions so as to prevent and treat SSH. This review aims to concisely sum up the role of gut microbiota in SSH and to discuss pertinent therapeutic strategies and clinical implications, thereby providing a valuable reference for further research and clinical practice in this area.